2011
DOI: 10.1155/2011/530397
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Monolayer Electrocatalysts for the Oxygen Reduction Reaction: Improvements Induced by Surface and Subsurface Modifications of Cores

Abstract: This paper demonstrates that the ORR activity of Pt ML electrocatalysts can be further improved by the modification of surface and subsurface of the core materials. The removal of surface low-coordination sites, generation (via addition or segregation) of an interlayer between Pt ML and the core, or the introduction of a second metal component to the subsurface layer of the core can further improve the ORR activity and/or stability of Pt ML electrocatalysts. These modifications generate the alternation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 76 publications
(97 reference statements)
0
17
0
2
Order By: Relevance
“…It has been long known that there is a volcano-shaped relationship between the ORR activity and the d-band center of transition metals where Pt lies nearest the top of the volcano [17,59,60]. To reach the peak performance, it has been argued that the d-band center of Pt needs to be downshifted by 0.1 -0.2 eV so as to weaken the interactions with oxygen intermediates [61]. In fact, in a prior study [37], we observed that the ORR activity of Pt/GQD nanocomposites reached the maximum with about 20% structural defects of the GQDs.…”
Section: Resultsmentioning
confidence: 99%
“…It has been long known that there is a volcano-shaped relationship between the ORR activity and the d-band center of transition metals where Pt lies nearest the top of the volcano [17,59,60]. To reach the peak performance, it has been argued that the d-band center of Pt needs to be downshifted by 0.1 -0.2 eV so as to weaken the interactions with oxygen intermediates [61]. In fact, in a prior study [37], we observed that the ORR activity of Pt/GQD nanocomposites reached the maximum with about 20% structural defects of the GQDs.…”
Section: Resultsmentioning
confidence: 99%
“…The most extensive and successful work in the field is due to Adzic and co-workers, who prepared finely tuned Pt monolayer catalysts with very high ORR intrinsic catalytic activity and the highest reported mass specific activity [65,66,79,[81][82][83]86,[88][89][90][91][92]96,[163][164][165][166][167][168][169][170][171][172][173][174][175][176][177][178][179][180]. In more detail, they have predicted theoretically (by means of Density Functional Theory (DFT) calculations) and confirmed experimentally that the most active catalyst for ORR is based on a Pt skin and a Pd-based core [81] which can be further improved by the use of a mixed Pt-noble metal skin and can reach an enhancement of mass activity in the 3-20-fold range [82].…”
Section: Oxygen Reductionmentioning
confidence: 99%
“…Das Pt 80 Pd 20 -Aerogel zeigt die hçchste massenspezifische Aktivität, die fünfmal hçher ist als jene des kommerziellen Pt/C-Katalysators.D ie Absenkung des d-Bandzentrums in den Legierungen, die häufig als ein Deskriptor des elektronischen Oberflächenzustands von ORR-Katalysatoren verwendet wird, zeigt das gleiche vulkanfçrmige Verhalten in den Pt n Pd 100Àn -Aerogelen. [112][113][114][115][116] Te sts der Alterungsbeständigkeit zufolge zeigen die bimetallischen Aerogele eine viel bessere Langzeitstabilitätals reine Pt-und Pd-Aerogele sowie Pt/C. Ein anderer interessanter Ansatz zur Herstellung hocheffizienter Elektrokatalysatoren ist die Bildung hohler Gelstrukturen aus vorab gebildeten, massiven Gelnetzwerken durch galvanischen Austausch.…”
Section: Metallaerogele -Ein Riesiger Entwicklungssprung Fürdie Elektunclassified